New technologies and tools to map and protect underwater treasures. (Research'eu results magazine)
Our seas and oceans are home to a tremendous amount of archaeological sites and artefacts. These invaluable witnesses to history are often difficult to locate, and even then experts are still faced with the question of whether to conserve them in situ or bring them to the surface. The SASMAP project has developed tools and techniques that will help solve both conundrums.